2018
DOI: 10.1016/j.bbi.2017.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Chronic social stress Ameliorates psoriasiform dermatitis through upregulation of the Hypothalamic-Pituitary-Adrenal axis

Abstract: Acute stress is a physiological response of an organism to adverse conditions, contributing to survival; however, persistence through time may lead to disease. Indeed, exacerbation of inflammatory conditions such as psoriasis has been reported to follow stressors in susceptible patients. Because chronic stress cannot ethically be elicited in patients under controlled laboratory conditions, we studied genetically modified mice that naturally develop psoriasiform dermatitis, and subjected them to an ethological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 83 publications
0
12
1
Order By: Relevance
“…Moreover, SLURP-1 was found to antagonize biological functions attributed to Chrna7 in patients with pancreatic cancer ( 95 ) or malignant melanoma ( 96 ). In skin plagued by an inflammatory disease this pro-inflammatory effect could hence have deleterious effects and worsen inflammation, while it could protect from cancer progression and potentially viral infections in other contexts ( 33 , 41 , 97 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SLURP-1 was found to antagonize biological functions attributed to Chrna7 in patients with pancreatic cancer ( 95 ) or malignant melanoma ( 96 ). In skin plagued by an inflammatory disease this pro-inflammatory effect could hence have deleterious effects and worsen inflammation, while it could protect from cancer progression and potentially viral infections in other contexts ( 33 , 41 , 97 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a hypothesis of the gut-brain-skin axis is being developed [68]. It has been proved that various skin disorders (urticarial, atopic dermatitis, psoriasis) have a strong correlation with the emotional status of the patient [69,70,71,72]. It has been shown that there is a negative influence on the immune system causing a greater risk of infections in patients subjected to mild to severe chronic stress [72].…”
Section: State Of Knowledgementioning
confidence: 99%
“…Moreover, we showed that the stress hormone GC (i.e., corticosterone) was increased in arthritic mice compared with that in control mice, and further increases were observed in stressed arthritic mice. Stress worsens skin diseases, such as psoriasis, and this phenomenon could be related to defects in the hypothalamic-pituitary-adrenal (HPA)-axis, altered glucocorticosteroid availability, or GCR dysfunction [27]. Because corticosterone generally has immunosuppressive effects, this hormone decreases IL-6 levels but stimulates; however, IL-2 plus corticosterone treatment increases IL-6 [28].…”
Section: Discussionmentioning
confidence: 99%